Tathwīr Lu’bah al-Ihtikār al-Lughah lī Istī’ābi al-Mufrodāt fī Ta’zīzi ar-Rūh at-Tanāfusiyah bī Istihdāmi Namūdzaj at-Ta’allum TGT - Manaf, Ghina Hajidah; Machmudah, Umi (UAS PRESS, 2025)
The background of this research addresses the issues of low vocabulary comprehension, passive student engagement, and suboptimal learning outcomes, necessitating media and learning methods that can enhance comprehension and motivation and improve learning results. The criteria for vocabulary mastery include understanding vocabulary meanings, connecting vocabulary with images, active vocabulary usage, developing new vocabulary, and accurate pronunciation. This study examines the process of implementing language monopoly media with the TGT (Teams-Games-Tournaments) learning model and explores its impact on students' vocabulary mastery. This research uses a qualitative method with descriptive analysis, drawing data from interviews, observations, and documentation. The findings indicate an improvement in students’ vocabulary comprehension, peer interaction, and enthusiasm for learning.